2015
DOI: 10.1039/c4nr05295a
|View full text |Cite
|
Sign up to set email alerts
|

Highly fluorescent C-dots obtained by pyrolysis of quaternary ammonium ions trapped in all-silica ITQ-29 zeolite

Abstract: Abstract.C-dots obtained in homogeneous phase may exhibit a broad particle size distribution. Formation of C-dots within nanometric reaction cavities could be a methodology to gain control on their size distribution. Among the various possibilities, in the present work, the cavities of small pore size zeolites have been used to confine C-dots generated by pyrolysis of the organic structure directing agent present in the synthesis of these crystalline aluminosilicates. To explore this methodology, ITQ-29 zeolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 53 publications
1
25
1
2
Order By: Relevance
“…Note that the selection of a suitable zeolite host is a key for pyrolysis of organo‐templated zeolites to generate CDs. Baldovi et al revealed that small pore zeolites ITQ‐29 (LTA) and ITQ‐12 (ITW) might facilitate the generation of CDs in zeolites during heating treatment, whereas medium or large pore zeolites silicalite (MFI) or pure silica Beta (*BEA) led the complete removal of occluded organic templates . Due to their high thermal stability, zeolite structures are almost retained in the reported CDs@zeolite composites, but CDs should be embedded in the interrupted nanospaces or reside on the external surface of zeolite matrices due to the larger size of CDs (≈2–6 nm) compared to the diameter of micropores (less than 2 nm).…”
Section: Synthesis Of Cds‐based Composite Materialsmentioning
confidence: 99%
“…Note that the selection of a suitable zeolite host is a key for pyrolysis of organo‐templated zeolites to generate CDs. Baldovi et al revealed that small pore zeolites ITQ‐29 (LTA) and ITQ‐12 (ITW) might facilitate the generation of CDs in zeolites during heating treatment, whereas medium or large pore zeolites silicalite (MFI) or pure silica Beta (*BEA) led the complete removal of occluded organic templates . Due to their high thermal stability, zeolite structures are almost retained in the reported CDs@zeolite composites, but CDs should be embedded in the interrupted nanospaces or reside on the external surface of zeolite matrices due to the larger size of CDs (≈2–6 nm) compared to the diameter of micropores (less than 2 nm).…”
Section: Synthesis Of Cds‐based Composite Materialsmentioning
confidence: 99%
“…5 In top-down approach, graphite and its derivatives are used to synthesize CDs through laser ablation, arc discharge and electrochemical oxidation. [21][22][23][24][25][26] In general, due to their simple and cost effective approach, bottom-up is more favourable than that of top-down techniques. [21][22][23][24][25][26] In general, due to their simple and cost effective approach, bottom-up is more favourable than that of top-down techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Baldovi et al employed small pore zeolites, ITQ-29 (LTA structure), and ITQ-12 (ITW structure) as rigid templates, tetramethylammonium hydroxide (TMAOH), 4-methyl-2,3,6,7tetrahydro-1H,5H-pyrido[3.2.1-ij]quinolinium hydroxide, and 1,3,4-trimethylimidazolium as the organic structure directing agent respectively. [159] After compressing to high pressure of 3 Ton cm −2 , these pelletized zeolite samples were calcined in inert atmosphere at required temperature. Carbon dots with particle size from 5 to 12 nm were obtained after etching the matrix of ITQ-29 and ITQ-12.…”
Section: Carbonization: In Situ Pyrolysis Of Organic Templates or Loamentioning
confidence: 99%